TRANSCRITICAL CO2 HEAT PUMP WITH EXPANDER-EJECTOR CYCLE - Sit B.; Timcenco D.; Sit M. (Problems of the Regional Energetics)
Heat pump with expander – ejector cycle, method of this cycle control of this cycle and the scheme of the heat pump with the second loop are presented in this paper.